A patient journey map study on time toxicity among young and middle-aged patients with breast cancer - Lixia Cui; Yuxiang Guan; Xiaoyan Chen; Fenglin Sun; Hao Wu; Yao Wang (Frontiers in Public Health, 2026)
Objective Based on the journey map, this study identified the multidimensional real-world experiences and core pain points of time toxicity among young and middle-aged breast cancer patients throughout the entire disease course, to provide a reference for alleviating patients’ time burden, optimizing the medical experience, and improving their quality of life. Methods A descriptive qualitative study was conducted. From August 2025 to February 2026, purposive sampling was used to recruit 19 young and middle-aged patients with breast neoplasms undergoing treatment at a tertiary Class A hospital in Anhui Province. Data from semi-structured in-depth interviews were analyzed using conventional content analysis. Results Participants experienced three sequential clinical phases including screening and diagnosis, treatment preparation, and treatment implementation. Their time toxicity experiences were categorized into four dimensions, namely behaviors, emotions, touchpoints and pain points, generating 19 phase-specific subthemes in total. Two cross-cutting core themes running through the full care pathway were further summarized from repeated shared experiences. Based on these findings, a patient journey map of time toxicity was developed for young and middle-aged patients with breast cancer. Conclusion The experience of time toxicity in young and middle-aged breast cancer patients is dynamic and phase-specific. It is characterized by passive waiting and information asymmetry during screening; decision-making pressure, role transition, and time conflict during treatment preparation; and cumulative time costs and social role deprivation during treatment implementation. We recommend phased and precise intervention strategies to better balance survival benefits and quality of life in this population.